Changes in host immunity following excision of a murine melanoma. - Bray, A. E. (Nature Publishing Group, 1975)
Changes in cell mediated and humoral immunity following the excision of a transplantable melanoma growing in the footpad of its syngeneic host, as measured by an in vitro cytotoxicity test, were assessed. Spleen cell cytotoxicity did not change significantly. Cells from the regional lymph nodes stimulated tumour growth before tumour excision. Three days following tumour excision this stimulatory effect was undetectable. Loss of serum factors capable of blocking the cytotoxicity of spleen cells occurred 24 h after tumour excision. Serum cytotoxicity increased after tumour excision to a maximum of the third day. Following tumour excision the rise in serum cytotoxicity and loss of regional lymph node tumour stimulation were concomitant with the loss of blocking activity.